Multiple associations of Alternaria species on high density apple (Malus × domestica) plantation system in Jammu and Kashmir, India - RASHID, MAHAPARA; WANI, SUHAIL QUYOOM; BHAT, ZAHOOR AHMAD; SHAH, MEHRAJ-UD-DIN; MIR, MOHD MAQBOOL; KHAN, IMRAN; LONE, F A; SAKIB, NAJMU; RATHER, MAHREENA FAROOQ; ZAFFAR, DAYIM; BHAT, MUSHTAQ AHMAD (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2021–2022 at Sher-e Kashmir University of Agricultural Sciences and Technology, Shalimar, Srinagar, Jammu and Kashmir to evalaute symptomatological development of Alternaria leaf blotch and spot of apple (Malus × domestica Borkh.) cultivars. The target of concern was to discern the specific Alternaria spp. intricately linked to manifestation of Alternaria fruit and leaf disease in apple trees under high density plantation system. Similarly, morpho-cultural characteristics of seven isolates were studied. Further, protein coding plasma membrane ATPase gene was used and the amplicon sequences were uploaded to GenBank and the accession numbers acquired after submissions for the ATPase were OQ355499, OQ222078, OQ333060 - OQ333064. The ATPase gene delimited all the isolates into three clades in which Clade-I contain sequences of Alternaria tenuissima. Clade-II consists sequences of Alternaria alternata while as Clade-III contains sequences of Alternaria arborescens. According to morphocultural, pathogenicity and molecular identification, the pathogens, viz. Alternaria alternata, Alternaria tenuissima, and Alternaria arborescens were found associated with apple leaf disease in India.